2020
DOI: 10.1108/imefm-08-2020-0419
|View full text |Cite
|
Sign up to set email alerts
|

Influential and intellectual structure of Islamic finance: a bibliometric review

Abstract: Purpose Islamic finance is an alternative approach of financial intermediation based on risk-sharing and asset-backed operations, which evolved substantially in recent years in academic research raising the need for quantitative studies to address the intellectual development and scientific performance of this field. This study aims to provide quantitative statistics and comprehensive review of the key influential and intellectual structure of Islamic finance literature. Design/methodology/approach The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 154 publications
(178 reference statements)
1
67
0
1
Order By: Relevance
“…We also use Microsoft Excel to generate editable tables and figure. The aforementioned software is among the best known and widely used to analyze bibliometric data (Nasir et al, 2021;Biancone et al, 2020;Handoko, 2020;Alshater et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also use Microsoft Excel to generate editable tables and figure. The aforementioned software is among the best known and widely used to analyze bibliometric data (Nasir et al, 2021;Biancone et al, 2020;Handoko, 2020;Alshater et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We use the Scopus database, which provides high capabilities for bibliometric research studies; it is also the largest esteemed database in social sciences (Nasir et al, 2021;Alshater et al, 2020). The study does not rely on other databases such as Web of Science (WOS) as…”
Section: Data Collection Strategymentioning
confidence: 99%
“…He has published many papers in high-quality journals, as well as books and book chapters; therefore, this qualification and experience makes IMEFM one of the top journals among Islamic economics and finance. Recent bibliometric studies (Alshater et al , 2020; Biancone et al , 2020; Khan et al , 2020b; Paltrinieri et al , 2019) also confirm the leading role IMEFM has in the Islamic finance literature.…”
Section: Introductionmentioning
confidence: 65%
“…While these databases allow deep analyses to be performed, several software tools such as VOSviewer and RStudio help researchers reveal findings in more user-friendly and visual ways. Several studies (Alshater et al , 2020; Bayram and Altarturi, 2020; Biancone et al , 2020; Khan et al , 2020a) are found to have conducted bibliometric analysis on English-written research on Islamic finance using international databases and programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation